A new morphological trait in forensic identification – middle phalangeal hair (MPH). (1st December 2016) - Krishan, Kewal; Kanchan, Tanuj
Middle phalangeal hairs (MPH) are present on the dorsal aspect of the middle phalange of the fingers except for the thumb. The MPH have been of interest to anthropologists, human biologists, clinicians, geneticists and anatomists in the past as a morphological trait of the human body. The anthropological value of MPH is well established in studying population variations, with implications for age, ancestry and sex differences. We are of the opinion that MPH may be used significantly for forensic identification purposes along with other morphological characteristics of the human body. MPH can be one of the individualistic features in comparing the ante-mortem and post-mortem records in mass fatality incidents and in establishing identity in forensic casework pertaining to CCTV images of the hand.